2008
DOI: 10.1074/jbc.m805514200
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3a Inhibits Cardiomyocyte Hypertrophy through Transactivating Catalase

Abstract: The forkhead transcription factor Foxo3a is able to inhibit cardiomyocyte hypertrophy. However, its underlying molecular mechanism remains to be fully understood. Our present study demonstrates that Foxo3a can regulate cardiomyocyte hypertrophy through transactivating catalase. Insulin was able to induce cardiomyocyte hypertrophy with an elevated level of reactive oxygen species (ROS). The antioxidant agents, including catalase and N-acetyl-L-cysteine, could inhibit cardiomyocyte hypertrophy induced by insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 51 publications
6
147
0
Order By: Relevance
“…It has been indicated that FoxO3a could retard cardiac hypertrophy 27. We next turned to explore whether expression of FoxO3a was altered by Rev.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that FoxO3a could retard cardiac hypertrophy 27. We next turned to explore whether expression of FoxO3a was altered by Rev.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. demonstrated that myocardin expression can be stimulated by ROS, and FoxO3a negatively regulates myocardin expression through controlling ROS levels 27. Recently, there were several reports suggesting that FoxO3a was closely controlled by miR‐155 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…For creating caFoxo3a transgenic mice, human caFoxo3a was obtained as we described 42 , and cloned to the vector pαMHC-clone26 (kindly provided by Dr Zhongzhou Yang) under the control of the α-myosin heavy chain (α-MHC) promoter. The primers used to generate caFoxo3a include, forward primer: 5′-ATGGCAGAGGCACCGGCTTCC-3′; reverse primer: 5′-TCAGCCTGGCACCCAGCTCTGAG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…We attempted to understand whether other downstream mediators of Foxo3a are involved in the fission and apoptotic programme. Catalase can be regulated by Foxo3a 42 ; we thus tested whether it can affect mitochondrial fission. Catalase suppressed mitochondrial fission and apoptosis ( Supplementary Fig.…”
Section: Foxo3a Inhibits Mitochondrial Fission Through Mir-484 and Fis1mentioning
confidence: 99%
“…There are two cellular mechanisms used to counteract ROS, which include: (1) antioxidant enzymes such as superoxide dismutase (SOD), catalase, and peroxidases, and (2) reductant species such as glutathione and thioredoxin (Berndt et al, 2007). Manganese SOD and catalase are enhanced by the forkhead transcription factor box O family (FoxOs) (Daitoku et al, 2004;Tan et al, 2008) which could be regulated by SIRT3 deacetylase activity (Tseng et al, 2013). Intriguingly, SIRT3 has been proven to ameliorate the cardiac hypertrophy by eliminating ROS through deacetylation and activating FoxO3a (Sundaresan et al, 2009).…”
Section: Role Of Sirt3 In Ameliorating Cardiac Hypertrophymentioning
confidence: 99%